Eucophylline, a tetracyclic vinylquinoline alkaloid from leuconotis eugenifolius - Deguchi, J.; Shoji, T.; Nugroho, A.E.; Hirasawa, Y.; Hosoya, T.; Shirota, O.; Awang, Khalijah; Hadi, A.H.A.; Morita, H. (American Chemical Society, 2010)
Eucophylline (1), a new tetracyclic vinylquinoline alkaloid, was isolated from the bark of Leuconotis eugenifolius together with leucophyllidine (2). The structure and absolute configuration of 1 were elucidated on the basis of 2D NMR correlations and simulated CD analysis. Leucophyllidine (2) showed iNOS inhibitory activity and decreased the iNOS protein expression dose-dependently.